Isolation and molecular characterization of Acanthamoeba and Balamuthia mandrillaris from combination shower units in Costa Rica - Retana Moreira, Lissette (2014)
Free living amoebae (FLA) are ubiquitous protozoa, which may behave as parasites under certain conditions. Four genera are recognized as causal agents of infections in humans and animals: Naegleria, Sappinia, Acanthamoeba and Balamuthia. This work determines the presence of FLA in combination shower units and employs molecular biology for the characterization of isolates. The morphological analy sis and partial sequencing of the 18S rDNA gene revealed the presence of Acanthamoeba genotype T4 in 30 % of the units sampled. In addition to Acanthamoeba cysts, trophozoites with morphological characteristics similar to Balamuthia were identified. PCR assay using the mitochondrial 16S rRNA gene as a target confirmed the identification of the amoeba as Balamuthia mandrillaris. Up to date, this is the first report of the isolation of B. mandrillaris in Central America and the fifth report worldwide.